Dynamics and limited cooperation in international environmental agreements - Larry S. Karp; Sandeep Sacheti (Fondazione Eni Enrico Mattei (FEEM), 1998)
The amount of cooperation needed to improve the welfare of signatories of International Environmental Agreements (IEAs), in the presence of market imperfections, depends on the characteristics of pollution. In a dynamic model, the conventional wisdom on the effect of free-riding needs to be modified for certain types of pollution problems. For local pollution problems, a sufficient level of free-riding actually promotes signatories' welfare. For global pollution problems, the conventional wisdom is correct insofar as free-riding makes it more difficult to form a successful IEA. However, for some global pollution problems, free-riding may disappear. A static model may overstate or understate the difficulty of forming a successful IEA. The effect of an IEA is sensitive to differences between the duration of the IEA and agents' planning horizon.
Keywords: F12; F42; Q28; 330; International environmental agreements; Environmental stocks; Dynamics; Free-riding; Umweltabkommen; Spieltheorie; Trittbrettfahrerverhalten; Dynamisches Modell; Theorie